2017
DOI: 10.1016/j.micres.2016.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Gut content microbiota of introduced bigheaded carps ( Hypophthalmichthys spp.) inhabiting the largest shallow lake in Central Europe

Abstract: Studying the microbiota in the alimentary tract of bigheaded carps (Hypophthalmichthys spp.) gained special interest recently, as these types of investigations on non-native fish species may lead to a better understanding of their ecological role and feeding habits in an invaded habitat. For microbiological examinations, bigheaded carp gut contents and water column samples from Lake Balaton (Hungary) were collected from spring to autumn in 2013.Denaturing Gradient Gel Electrophoresis (DGGE) and pyrosequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 82 publications
0
23
1
1
Order By: Relevance
“…In this study, core OTUs refer to the ones found in each individual midgut sample. The effect of the surrounding water was not studied since it is expected to be insignificant for the GITM diversity as shown previously [ 20 , 21 , 22 , 23 ]. A single water sampling on the same day of the midgut sampling of the investigated fish individuals, would not be so informative due to the following two factors: 1) marine bacterioplankton is characterized by strong variation in short (e.g., [ 24 , 25 ]) and longer [ 26 , 27 , 28 , 29 ] time scales, and 2) the life cycle of farmed S. aurata and D. labrax spans over several months.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, core OTUs refer to the ones found in each individual midgut sample. The effect of the surrounding water was not studied since it is expected to be insignificant for the GITM diversity as shown previously [ 20 , 21 , 22 , 23 ]. A single water sampling on the same day of the midgut sampling of the investigated fish individuals, would not be so informative due to the following two factors: 1) marine bacterioplankton is characterized by strong variation in short (e.g., [ 24 , 25 ]) and longer [ 26 , 27 , 28 , 29 ] time scales, and 2) the life cycle of farmed S. aurata and D. labrax spans over several months.…”
Section: Resultsmentioning
confidence: 99%
“…Anaerobic Cetobacterium spp. promotes decomposition of consumed organic debris, phytoplankton, or zooplankton (Borsodi et al., ). This species was also common in intestinal tracts of goldfish, common carp, grass carp, ayu, tilapia, zebrafish, rainbow trout, channel catfish, largemouth bass, and bluegill (Adeoye et al., ; Etyemez & Balcázar, ; Larsen, Mohammed, & Arias, ; Roeselers et al., ; Tsuchiya, Sakata, & Sugita, ; Van Kessel et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are also in accordance with a long‐term study on the seasonal patterns of free‐living bacteria of the mesoeutrophic Lake Tiefwaren (Germany) where high abundance of the lineage “ Candidatus Planktophila limnetica” was retrieved by DGGE method (Rösel, Allgaier, & Grossart, ). In another study, season independent presence of DGGE band sequences closely related to Candidatus Planktophila limnetica was detected in the water of Lake Balaton (Hungary), and the high abundance of this lineage was verified by pyrosequencing (Borsodi et al, ). Due to the lack of a pure culture, the ecological role of these freshwater Actinobacteria has not been clarified yet (Jezbera et al, ).…”
Section: Discussionmentioning
confidence: 94%